Escherichia coli HdeB Is an Acid Stress Chaperone - Kern, Renee (2006)
We cloned, expressed, and purified the hdeB gene product, which belongs to the hdeAB acid stress operon. We extracted HdeB from bacteria by the osmotic-shock procedure and purified it to homogeneity by ionexchange chromatography and hydroxyapatite chromatography. Its identity was confirmed by mass spectrometry analysis. HdeB has a molecular mass of 10 kDa in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, which matches its expected molecular mass. We purified the acid stress chaperone HdeA in parallel in order to compare the two chaperones. The hdeA and hdeB mutants both display reduced viability upon acid stress, and only the HdeA/HdeB expression plasmid can restore their viability to close to the wild-type level, suggesting that both proteins are required for optimal protection of the bacterial periplasm against acid stress. Periplasmic extracts from both mutants aggregate at acidic pH, suggesting that HdeA and HdeB are required for protein solubilization. At pH 2, the aggregation of periplasmic extracts is prevented by the addition of HdeA, as previously reported, but is only slightly reduced by HdeB. At pH 3, however, HdeB is more efficient than HdeA in preventing periplasmic-protein aggregation. The solubilization of several model substrate proteins at acidic pH supports the hypothesis that, in vitro, HdeA plays a major role in protein solubilization at pH 2 and that both proteins are involved in protein solubilization at pH 3. Like HdeA, HdeB exposes hydrophobic surfaces at acidic pH, in accordance with the appearance of its chaperone properties at acidic pH. HdeB, like HdeA, dissociates from dimers at neutral pH into monomers at acidic pHs, but its dissociation is complete at pH 3 whereas that of HdeA is complete at a more acidic pH. Thus, we can conclude that Escherichia coli possesses two acid stress chaperones that prevent periplasmic-protein aggregation at acidic pH.